Occupational mental health among nurses : a conceptual and analytical framework - Behrend, Brad (My University, 2011)
A poster containing visuals and text describing an undergraduate research project completed at the University of Wisconsin--Whitewater. This study assessed stress, burnout, depression, and working conditions among nurses and developed insights on mental health outcomes and organizational policies that affect stress levels by analyzing data gathered from completed questionnaires.
This file was last viewed in Adobe Reader 10.0.1
Keywords: Nursing--Psychological aspects; Nurses--Mental health; Nurses--Job stress; Nursing--Employment